Staged management of a large ischemic heel ulcer in a diabetes patient: a case report - Chen, Yuedong; Yang, Hui; Wang, Wei; Chen, Yinchen; Jiang, Dong; Li, Yihui; Li, Liyi; Yang, Wengbo; Wang, Aiping (Frontiers in Endocrinology, 2023)
Heel ulcer is one of the severe complication of patients with diabetes mellitus which poses a high risk for foot infection and amputation, especially in patients with peripheral arterial disease and neuropathy. Researchers have searched for new treatments for treating diabetic foot ulcers in recent years. In this case report, we demonstrated the treatment of large ischemic ulcers for the first time in diabetic patients. The overall treatment goal of this patient was designed to improve blood supply to her diseased lower extremities and close the ulcer. This two-stage reconstruction approach resulted in an ulcer-free, stable, plantigrade foot at postoperative follow-up.